2009
DOI: 10.1128/jvi.01370-09
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) Type 18 Induces Extended Growth in Primary Human Cervical, Tonsillar, or Foreskin Keratinocytes More Effectively than Other High-Risk Mucosal HPVs

Abstract: Mucosal high-risk (HR) human papillomaviruses (HPVs) that cause cervical and other anogenital cancers also are found in ϳ25% of head and neck carcinomas (HNCs), especially those arising in the oropharynx and the tonsils. While many HR HPV types are common in anogenital cancer, over 90% of HPV-positive HNCs harbor HPV type 16 (HPV-16). Using a quantitative colony-forming assay, we compared the ability of fulllength mucosal HPV genomes, i.e., the low-risk HPV-11 and HR HPV-16, -18, and -31, to persist in and alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 70 publications
2
36
0
3
Order By: Relevance
“…However, the potential existence of type-dependent mechanisms of immune escape and the role of the tumor microenvironment are still largely unexplored. Furthermore, we cannot rule out the possibility that the oncogenicity of HPV45, -51, -52, and -59 is epithelium dependent, although no such cell type dependency was demonstrated for HPV11, -16, -18, and -31 (55).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the potential existence of type-dependent mechanisms of immune escape and the role of the tumor microenvironment are still largely unexplored. Furthermore, we cannot rule out the possibility that the oncogenicity of HPV45, -51, -52, and -59 is epithelium dependent, although no such cell type dependency was demonstrated for HPV11, -16, -18, and -31 (55).…”
Section: Discussionmentioning
confidence: 86%
“…Although this observation was surprising given its relatively high prevalence in cervical cancer worldwide (7), one may speculate that HPV45 is more effective in the induction of subsequent transformation events, such as anchorage-independent growth and colony formation, as was shown for HPV18 compared to HPV16 (55).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies with HPV-E6/E7 immortalized keratinocytes and raft cultures have shown that a persistent HPV infection is not sufficient for malignant transformation. [14][15][16] This transformation can be achieved by treating them for example with tobacco mutagens. 17 However, patients with HPV-positive carcinomas are significantly less likely found in smokers and drinkers.…”
mentioning
confidence: 99%
“…Advances in keratinocyte culture techniques have permitted the study of the life cycle of HR HPV types that replicate efficiently and persist in primary human keratinocytes, such as HPV-16, HPV-31 (32,34,35), and to a more limited extent HPV-18 (28,36). However, relatively little is known about the progression of the infected cell toward a malignant phenotype in vivo or in culture.…”
mentioning
confidence: 99%
“…In this study, we compared the physical state of HPV DNAs, mRNA sequences, and spliced structures in nine HPV-16-containing HNC tumors to those found in sets of isogenic clones of primary human keratinocytes derived from tonsillar or foreskin epithelia immortalized by the introduction of plasmid HPV-16 genomes (28,49). These culture reagents and assays provide the necessary tools to answer questions regarding viral integration and oncogenic progression that otherwise might not be effectively addressed with clinical material alone and offer an effective model system for examining HR HPV integration and its role in HPV-associated carcinogenesis.…”
mentioning
confidence: 99%